Production of jelly candy using sweet potato (Ipomoea batatas) starch - Dacanay, Abigail P. (2010)
Sweet potato is one of the most important food sources in the Philippines. Nowadays, the demand for sweet potato has dramatically increased with the realization of its potential for commercial applications. In this study, sweet potato starch was used as a partial substitute for cornstarch in the production of jelly candy. Four formulations, 35%, 50%, 75% and 95%, were subjected to a Preference test to determine the optimum sweet potato starch substitution. The samples with 35%, 50% and 75% substitution, which had high preference, were not significantly different from each other but were significantly different from the sample with 95% sweet potato starch substitution. Hence, the 35% further evaluated for its sensorym= physicochemical and microbial properties. In the consumer acceptance test, the sensory attributes of the jelly candy, which include the overall liking, appearance, texture, flavor and aftertaste were acceptable based on the Sign test.